2008
DOI: 10.1177/105382590703000308
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Exploration of the Influence of Short-Term Adventure-Based Expeditions on Levels of Resilience

Abstract: blizzards, and among the many pictures that come to mind is one of individuals surviving these catastrophes and "bouncing back" in the aftermath. From a theoretical perspective, this "bouncing back" has typically been linked to the concept of resiliency. Defined as an individual constellation of characteristics and capacities that mitigate the impact of biological, psychological and social factors that threaten an individual's health (Kaplan, 1999; Ungar, Dumond, & Mc-Donald, 2005), resiliency represents one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…And similar to the outcomes in wilderness, improvement is maintained at follow-up one year later. These studies provide support for the claim that private-pay residential programs and wilderness therapy programs provide a lasting benefit (Behrens, 2006;Behrens et al, 2010;Behrens & Satterfield, 2007;Bettmann, 2007;Bettmann, Demong, & Jasperson, 2008;Davis-Berman & Berman, 1993;Ewert & Yoshino, 2008).…”
Section: Research Efforts Across Programssupporting
confidence: 52%
“…And similar to the outcomes in wilderness, improvement is maintained at follow-up one year later. These studies provide support for the claim that private-pay residential programs and wilderness therapy programs provide a lasting benefit (Behrens, 2006;Behrens et al, 2010;Behrens & Satterfield, 2007;Bettmann, 2007;Bettmann, Demong, & Jasperson, 2008;Davis-Berman & Berman, 1993;Ewert & Yoshino, 2008).…”
Section: Research Efforts Across Programssupporting
confidence: 52%
“…In the modern literature, there is some debate about the extent to which the lessons learned on expedition transfer to more mundane situations in participants' home lives. Nonetheless, it has been argued that short-term expedition experiences can produce a longterm personality change (Ewert & Yoshino, 2007;Takano, 2010). Similarly, recent work by Sayer (2011) suggests that change of understanding and world view typically takes time and does not happen 'overnight'.…”
Section: Insert Table 2 Herementioning
confidence: 99%
“…Moreover, there is evidence that expedition friendships often take on a meaningful quality that lies in stark contrast to those developed within normal social structures. One study found a significant self-reported positive response to statements such as "I can deal with whatever comes in the future" (Ewert & Yoshino, 2007). Others link this increase in selfreliance to the degree of the participants' involvement in the practical operation of the expedition (Ashby, 1999;Kennedy, 1992).…”
Section: Insert Table 2 Herementioning
confidence: 99%
“…A recent study examined the application of attachment theory to working with adults in wilderness therapy (Bettmann & Jasperson, 2008), while others primarily examined the impact of nonclinical wilderness adventures with adults (Goldenberg & Pronsolino, 2008;Jostad, Paisley, & Gookin, 2012;Paxton & McAvoy, 2000) or as an adjunct to inpatient treatment for survivors of combat-related PTSD (Hyer, Boyd, Scurfield, Smith, & Burke, 1996). Similar studies explored the impact of wilderness exposure on sense of community (Breunig et al, 2008) or resilience (Ewert & Yoshino, 2008).…”
mentioning
confidence: 97%